Threshold criteria for incipient sediment motion on an inclined bedform in the presence of oscillating-grid turbulence - Wan Mohtar, Wan Hanna Melini; Munro, Richard J. (American Institute of Physics, 2013)
Here, we report laboratory experiments to investigate the threshold criteria for incipient sediment motion in the presence of oscillating-grid turbulence, with the bed slope inclined at angles between the horizontal and the repose limit for the sediment. A set of nine mono-disperse sediment types was used with size ranges normally associated with either the hydraulically-smooth or transitional regimes. Measurements of the (turbulent) fluid velocity field, in the region between the grid and bedform's surface, were obtained using two-dimensional particle imaging velocimetry. Statistical analysis of the velocity data showed that the turbulence had a anisotropic structure, due to the net transfer of energy from the normal to the tangential velocity components in the near-bed region, and that the fluctuations were dominant compared to the secondary mean flow. The sediment threshold criteria for horizontal bedforms were compared with, and found to be in good qualitative agreement with the standard Shields curve. For non-horizontal bedforms, the bed mobility was found to increase with increasing bed slope, and the threshold criteria were compared with previously-reported theoretical models, based on simple force-balance arguments.